Penertiban Pedagang Kaki Lima oleh Kewenangan Pemko Batam - Hutauruk, Rufinus Hotmaulana; Medi, Jepri (Journal of Law and Policy Transformation, 2016)
The purpose of this research was to determine the authority of Batam City government in policing street vendors which stand on the land rights of exploitation of Batam Concession Entity. It is also to determine what factors impede the Batam City Government in policing street vendors which stand on the land rights of exploitation of Batam Concession Entity. The results of this research concludes that the Batam City Government has a mandatory authority in policing street vendors which stand on the land rights of the land management exploitation Batam. The factors impede the Batam City Government in policing street vendors arise from the duality of authority on the tenure rights to land. The solutions suggested is that the Batam Government City should take action to streamline the implementation eventually make an act of synergy between the parties government took office with government officials.   Tujuan penelitian ini adalah untuk mengetahui kewenangan Pemko Batam dalam penertiban pedagang kaki lima yang berdiri di atas lahan hak pengelolaan BP Batam, untuk mengetahui Faktor-faktor apa yang menjadi Hambatan Bagi Pemko Batam dalam penertiban pedagang kaki lima  yang berdiri di atas lahan hak pengelolaan Lahan  Badan Pengusahaan Batam Batam dan untuk mengetahui solusi apa yang dapat dilakukan Pemerintah Kota Batam dalam Penertiban Pedagang Kaki Lima yang Berdiri di Atas Lahan Hak Pengelolaan Lahan  Badan Pengusahaan Batam. Hasil dari penelitian ini adalah Kewenangan Pemko Batam dalam Penertiban Pedagang Kaki Lima di Atas Lahan Hak Pengelolaan Badan Pengusahaan Batam menjadi kewenangan wajib yang harus dilakukan.